Linac and damping ring designs of the future circular e+e− collider of CERN - Oğur, Salim. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
CERN has started the design of a 98 km circular positron-electron collider as a ﬁrst step of the global Future Circular Collider (FCC) project since 2014. The FCCe+e− is being designed to furnish high luminosities for Z, W, H, and t¯ t particles with diﬀerent energies and currents in the collider and it will restore the charge decrease due to collisions, scatterings etc. via quasi-continuous top-up injection. However, the pre injector chain will keep its present course yet cycle distinctly through the 4 operational stages in the collider. The injector complex will consist of a 6 GeV S-Band linac, a damping ring at 1.54 GeV and pre-booster ring to reach 20 GeV for injection to the main booster, which is located in the same tunnel as the collider, which will accelerate the beams to the ﬁnal energies for collisions. As an alternative option to the pre-booster ring, a 20 GeV linac is also considered. The positrons will be created by impinging onto a hybrid target inside the linac at 4.46 GeV and accelerated in the remaining part of the linac up to 1.54 GeV and get matched to be transferred into the damping ring for radiation damping. The designs of the linacs and damping ring will be the foci of this thesis, as well as the optimisation of bunch schedules of the whole injector complex up to the collider. The beam optics designs are partially applied at SuperKEKB linac of KEK by hands-on operations. The beam based misalignment studies and beam jitter source survey have taken place which are also presented in this thesis.
Keywords: Particle accelerators.; Colliders (Nuclear physics)